A Analisis Kesalahan Siswa dalam Menyelesaikan Soal Asesmen Kompetensi Minimum (AKM) Keliling dan Luas Bangun Datar Berdasarkan Teori Kesalahan Newman - Wahyuni, Yeni Tri; Rufiana, Intan Sari; Faizah, Siti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Numeration in AKM which is contextualized in various types of questions has the aim of evaluating student competence. So it is necessary to know where students' mistakes are, to improve the way students solve mathematical problems. The aim of this research is to describe students' mistakes in solving problems on AKM questions related to perimeter and area of ​​flat shapes. This research is descriptive qualitative research. The research subjects chosen in this study were based on consideration of students' mathematical ability test results in the high (80 to 90), medium (65 to 80) and low (less than 65) categories. Then 3 students were randomly selected for each ability level, with details 1 student with high ability, 1 student with medium ability, and 1 student with low ability. Data collection techniques in this research were tests, interviews and documentation. Data analysis techniques used the Miles and Huberman model did not experience errors in solving the AKM questions on flat figures, perimeter and area. On the other hand, students with low mathematical abilities tended to experience errors in understanding the problems, carrying out problem transformations, and in the work process.